Potential Degradation of SARA (Saturated, Aromatics, Resinics, Asphaltenes) Fractions of Crude Oil by Reservoir Indigenous Bacteria from South Sumatera (Indonesian Society for microbiology, 2017)
MEOR (Microbial Enhanced Oil Recovery) technology utilizes metabolic activity of microorganisms such as degradation of hydrocarbon fractions which alters oil characteristics to facilitate and increase oil recovery from reservoir. This research focused on isolation of indigenous hydrocarbonoclastic bacteria that were capable of degrading SARA (Saturated, Aromatic, Resinic, Asphaltenes) fractions of crude oil to be utilized in MEOR. Sequential isolation of hydrocarbonoclastic bacteria were conducted using Nutrient Broth and Stone Mineral oSalt Solution medium supplemented with 2% (v/v) crude oil and 0.1% (w/v) yeast extract and incubated at 50C, 120 rpm agitation. Isolates retrieved were screened based on its activity to degrade crude oil, indicated by resazurin assay result. Physical and chemical characteristics of crude oil altered by selected isolates were observed using column chromatography, biometric test, GC-MS analysis, IFT and viscosity measurements. Isolates with the best degradation activity were identified with 16S rRNA gene sequencing. Among thirty-one bacterial isolates obtained from sequential isolation, six isolates exhibited high oil degrading ability. SARA assay showed degradation activity of those isolates to each of SARA fraction were around 6-70%.Â This degradation was followed by significant CO production ranging from 2000-4000 mg (value of p<0.05). Microbial 2 degradation activity exhibited changes in chemical and physical characteristics of hydrocarbons showed by changes in composition of SARA fraction, decreased viscosity and IFT of crude oil 17-31%. This research identified three isolates with the best hydrocarbon fraction degrading ability were identified as different strain of Bacillus licheniformis and confirmed their high potential to be utilized in MEOR technology.